(untitled) (Research, Society and Development, 2020)
This study evaluated the effect of tooth whitening on resin composites (RC) on roughness, microhardness and flexural strength. There were three RC: one Bulk Fill type resin (Filtek Bulk Fill) and two conventional, Filtek Z350 (Z350) and Z250 (Z250). Twenty-four bar-shaped specimens were made for each RC. First, the initial roughness and microhardness were evaluated; thus, the RC were subdivided into 3 other groups, according to treatments: control group (C), this did not receive bleaching treatment; home bleaching with 10% carbamide peroxide (10%CP) (Opalescence PF), 8h/14 days; home-office bleaching with 40% hydrogen peroxide (40%HP) (Opalescence Boost PF) 3 ´ 15 minutes for 3 days at 48 hour intervals. After treatments, roughness and microhardness were again evaluated and then the samples submitted to the three-point flexural test. Data were tabulated, normality assessed, then submitted to ANOVA followed Tukey’s test (p <0.05). The results showed that the bleaching change the roughness of RC, but 10%CP had a significant increase. The gel concentration does not influence microhardness and flexural strength. After bleaching, Z350 has a lower elastic modulus. Based in the results obtained, could be concluded that the different bleachings did not promote significant changes on the RC studied.